2014
DOI: 10.1007/s00240-014-0659-y
|View full text |Cite
|
Sign up to set email alerts
|

Use of flexible ureteroscopy in the clinical practice for the treatment of renal stones: results from a large European survey conducted by the EAU Young Academic Urologists-Working Party on Endourology and Urolithiasis

Abstract: Treatment of renal stones using flexible ureteroscopy (fURS) is increasingly common despite the poor evidence in literature supporting its use and indications. With this study, we wanted to investigate the current use and indication of fURS for the treatment of renal stones in the clinical practice across the European countries. A survey was conducted using an emailed questionnaire consisting of 21 items; 2,894 recipients were selected via the EAU membership database. The questionnaires were collected through … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 23 publications
2
11
0
Order By: Relevance
“…In a survey of flexible URS practice patterns among urologists conducted by the EAU, a UAS was preferred by 71% and approximately 50% of all respondents reported retrieval of larger fragments using such an approach. 63 This survey also found that senior urologists were less likely to perform retrieval than younger urologists. Nevertheless, whether or not active retrieval actually improves the SFR in patients under going stone surgery remains unproven.…”
Section: Active Retrieval Of Fragmentsmentioning
confidence: 93%
“…In a survey of flexible URS practice patterns among urologists conducted by the EAU, a UAS was preferred by 71% and approximately 50% of all respondents reported retrieval of larger fragments using such an approach. 63 This survey also found that senior urologists were less likely to perform retrieval than younger urologists. Nevertheless, whether or not active retrieval actually improves the SFR in patients under going stone surgery remains unproven.…”
Section: Active Retrieval Of Fragmentsmentioning
confidence: 93%
“…1 Despite recent population-level evidence demonstrating increasing utilization of fURS, [2][3][4] little information exists on contemporary practice patterns of fURS for the treatment of renal calculi. 5 While guidelines recommend fURS for treating renal stones <1.5 cm, 6 considerable differences exists among urologists in the technique, use, and indications of fURS. In particular, the variation in the use of disposable equipment, such as ureteral access sheaths (UAS) or nitinol retrieval devices, and the utilization of more powerful high-watt holmium laser systems in the modern era of fURS, have not been thoroughly evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the European Association of Urology (EAU) conducted a survey on the use of fURS for the treatment of renal calculi in Europe. 5 To study a broader collection of urologists throughout the world, we modified this questionnaire and surveyed members of the Endourology Society about multiple facets of renal calculi treatment using fURS. Our specific aim was to explore differences in the fURS technique and practice among endourologists.…”
Section: Introductionmentioning
confidence: 99%
“…Percutaneous nephrolithotomy (PCNL) and retrograde intrarenal surgery (RIRS) are two common and widely used alternative interventions for the treatment of renal stones. Flexible Institute of Computational Science, Universita della Svizzera Italiana, 6900 Lugano, Switzerland ureteroscopy by RIRS is a popular intervention for the treatment of renal stones, and it has been widely used over the last two decades, particularly in Europe [7].The 2014 Urolithiasis Guideline of the European Association of Urology prescribes PCNL as the preferred treatment for renal stones over 2 cm in stone diameter [8], as it has high stone-free rates. However, it has been observed that PCNL in certain cases also lead to a high risk of postoperative fever, such as sepsis, which is a life-threatening and complicated infection.…”
Section: Introductionmentioning
confidence: 99%